A novel UPLC–MS/MS method for simultaneous quantification of rhein, emodin, berberine and baicalin in rat plasma and its application in a pharmacokinetic study. (May 2012) - Huang, Ping; Gao, Jing-wen; Shi, Zhan; Zou, Jia-li; Lu, Ya-song; Yuan, Yue-mei; Yao, Mei-cun
Background: Dahuang Huanglian Xiexin Decoction (DHXD) is a classical formula in traditional Chinese medicines. In this study, a novel UPLC-MS/MS method was developed for the simultaneous quantification of rhein, emodin, berberine and baicalin, the major bioactive compounds of DHXD in rat plasma.Results: The method possessed high sensitivity and ultrashort analysis time (7 min). Linearity, accuracy, precision and extraction recovery of four analytes were all satisfactory. The method was then successfully applied in a pharmacokinetic study of four bioactive components after a single oral administration of DHXD extract to rats.Conclusion: The method was applicable for simultaneous bioanalysis of rhein, emodin, berberine and baicalin.